Content Analysis of Sociology Textbooks Using Bloom's Taxonomy in SMAN 1 Featured Indralaya Utara - Fitri, Fitri; Alfitri, Alfitri (Laboratorium Sosiologi FISIP Universitas Jember, 2019)
This study aims to discuss the contents of textbooks on sociology subjects at the high school level. This study uses descriptive qualitative methods. Data collection techniques are carried out through observation, interviews and literature. The data analysis technique used is content analysis, namely the researcher reads and develops the sociology textbooks written by Srikandi four. The results of the study showed that the contents of the sociology textbooks written by Srikandi four were more dominant in the cognitive domain (knowledge). Keywords: Text Textbooks, Sociology, Bloom Taxonomy Referensi: Agustina, Eka Sofia. 2011. Materi Ajar BTBI. Lampung: Universitas Lampung. Arikunto, Suharsimi. 2009. Dasar-dasar Evaluasi Pendidikan. Jakarta: Bumi Aksara. Anjarsari, Eka. 2012. Penilaian Kualitas Buku Teks Pelajaran Geografi Sebagai SumberBelajar Bagi Siswa Sma Kelas Xi Di Kabupaten Temanggung. Skripsi. Universitas Negeri Semarang. Banowati, Eva. 2007. Buku Teks Dalam Pembelajaran Geografi di Kota Semarang‟. Dalam Jurnal Geografi. Vol. 4. No. 2. Hal. 147-158. http:// journal. unnes. ac.id/ index.php/JG/article/view/106/108 diunduh pada 18 April 2019. Jitendra, Nolet, Xin, Gomez, Renouf, Iskold, &DaCosta (2001) An Analysis Of Middle School Geography Textbooks: Implication For Students With Learning Problem. Lee, J., & Catling, S.2016. Some perceptions and practices of English geography textbook authors. International Research in Geographical and Environmental Education, 25,5067. Ngalim, Purwanto. 2000. Ilmu Pendidikan Teoretis dan Praktis. Bandung: P1 Remadja Karya. Shamir, A., Zion, M., Levi. 2008. Peer Tutoring, Metacognitive Processes and Multimedia Problem-based Learning: The Effect of Mediation Trainingon Critical Thinking. Journal Science Education Technology. 17:384– 398. Tarigan, HG dan Diago Tarigan. 1990. Telaah Buku Teks Bahasa Indonesia. Bandung. Angkasa. Walkington, H., Dyer, S., Solem, M., Haigh, M.,&Waddington. 2017. A capabilities approach to higher education: geo capabilities and implications for geography curricula. Journal of Geography in Higher Education, DOI:10.1080/03098265.2017.1379060.